Internal control effectiveness in a property development company: a case study of TH Properties Sdn.Bhd. / Shazlina Abdul Jalil - Abdul Jalil, Shazlina (2014)
Internal controls exist in order to promote operational efficiency and effectiveness, provide reliable financial information, safeguard assets and records, encourage adherence to prescribed policies and comply with regulatory agencies. The basic concepts of internal controls indicate that the management, not auditors, must establish and maintain the entity's controls; the internal control structure should provide reasonable assurance that financial reports are correctly stated.This study is done to promote and understanding of the internal control system based on the Committee of Sponsoring Organization (COSO) Internal Control - Integrated\ Framework. The study is to significantly highlight among the most important aspect of internal control which includes the control environment, or "Tone at the Top." The attitudes and behaviour of senior executive management and the Board of Directors is essential to a healthy system of internal control. An internal control environment consists of management's philosophy and operating style that includes the tone at the top that is set by the board and senior executives of an entity. It should also include the integrity and ethical values of the employees, a proper risk assessment and evaluations, an organizational structure that promotes separation of duties and decreases conflicts of interest, the assignment of authority and responsibility so people understand their roles and responsibilities, having competent, knowledgeable personnel who are informed of policies and procedures and have the proper training and ongoing development, communication of pertinent issues and information systems that have built-in business rules and controls. This study is done through primary data assessment. Questionnaires were distributed among the management team of TH Properties Sdn. Bhd. to get a better feedback and understanding on the current internal control system implemented in the organization. This is then compared with the COSO framework to understand the effectiveness of internal control system and the implementation of the internal control system in the organization. This study promotes a better view and understanding over the internal control effectiveness of TH Properties Sdn. Bhd. This is to ensure a better understanding of the current internal control system implemented in the organization and promote to improvisation for the organization.